Analysis and Experimental Verification of a Single-Phase, Quasi-Halbach Magnetised Tubular Permanent Magnet Motor - Ibrahim, Taib; Wang, Jiabin; Howe, Dave (2008)
The paper describes the analysis and experimental verification of a short-stroke, single-phase, quasi-Halbach magnetised tubular permanent magnet motor in which the magnets may be mounted on either a magnetic or non-magnetic support tube. Analytical solutions for the magnetic field distribution in the airspace and magnet regions are established in the cylindrical coordinate system. The analytically predicted static performance of a prototype motor is validated by finite element predictions and measurements.